A new species of the mud shrimp genus Axianassa Schmitt, 1924 (Decapoda: Gebiidea: Laomediidae) from the Ryukyu Islands, southern Japan - Komai, Tomoyuki; Fujita, Yoshihisa (Zootaxa, 2019)
A new species of the laomediid mud shrimp genus Axianassa Schmitt, 1924, A. planioculus, is described and illustrated on the basis of a single male specimen from intertidal muddy sand flat of Kabira Bay, Ishigaki Island, southern Ryukyu Islands, Japan. Axianassa planioculus n. sp. is morphologically closest to A. mineri Boone, 1931, known from Pacific Panama, among the 11 known congeners, but is readily distinguished from the latter by the eyes being dorsally concealed by the rostrum, the subovate telson, the unarmed carpus of the maxilliped 3 and the unarmed uropodal endopod. The discovery of a new mud-shrimp species in an easily accessible habitat indicates that the shallow-water infaunal decapods are still relatively poorly known. A partial segment of the mitochondrial 16S rRNA gene was sequenced from the holotype for future genetic studies.